“Jurnalistik Itu Asik” pada Pelajar Ipnu-Ippnu Ranting Desa Trikarso dan Karangtaruna Desa Trikarso - Taufik Hidayat; Muchlas Abror; Hellaisna Nur’aini Garwan; Rosita Sofyaningrum; Moch. Abdul Ghonny N. R.; Kukuh Trisnadi; Much. Ridho (Abdibaraya: Jurnal Pengabdian Masyarakat, 2022)
The lack of knowledge about journalistic writing, the lack of publication of news in the village, the lack of awareness from the community about writing a news story are the reasons for implementing the thematic service for the Kebumen UMNU KKN with the theme "Journalism is Fun". This training is a form of implementation of the Tri Dharma of Higher Education, namely Community Service and also provides learning experiences about journalistic writing to the community, especially IPNU-IPPNU students of Trikarso Branch and Trikarso Village Karangtaruna. Community service activities in the form of journalistic training include the delivery of material on Introductory Journalism Materials, News Writing Techniques, and Article Writing Techniques. The presentation of the training was carried out using lecture, question and answer methods, demonstrations. The participants also carried out practice in the form of news hunting and continued with compiling and writing news. The parties involved as speakers in this activity were Fathurohman Wahid as the editor of Kebumen Talk, Mugiono as the Head of Head of Kebumen Talk and Aby, a Tidar University student. Keywords: Community Service, Journalism, Trikarso